IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA SEKOLAH PENGGERAK DI KOTA PALEMBANG: STUDI KASUS SMPN 20 dan SMPN 45 PALEMBANG: Penelitian Skripsi - Novita, Dina; Chotimah, Umi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project at two Driving Schools in Palembang, namely SMPN 20 and SMPN 45. Using a mixed-methods approach, quantitative data from questionnaires measured Pancasila Student Profile Reinforcement Project understanding and the achievement of Pancasila Student Profile dimensions, while interviews and documentation provided qualitative data on the planning, implementation, and evaluation of the Pancasila Student Profile Strengthening Project. The results show that both schools achieved